For an information-based transforming praxis: dialogues with Marxism on the basis of the Information Science history - Silva, Carlos Robson Souza da; Cavalcante, Luciane de Fátima Beckman (Ciência da Informação em Revista, 2024)
It discusses the relationships between the epistemological history of Information Science and contemporary capitalism in order to propose an information-based transformative praxis. It aims to outline the Information Science’s origin and historical development; analyze the relationship between the development of Information Science and the restructuring of contemporary capitalism; and discuss how it is possible to adopt assumptions and from the Marxist thought in the search for a transforming praxis based on information. This is a theoretical, exploratory and qualitative research, based on bibliographic sources. It discusses the historical relations of Information Science with Positivism and Postmodernism and discusses how the relations can be associated with the contemporary development of capitalism. It concludes that in Marxist thought, Information Science can find a theoretical, epistemological and methodological reference capable of re-humanizing information, calling into question exclusionary societal projects and developing an information-based transformative praxis.